Positional Arrangements of Waste Exhaust Gas Ducts of C-Type Balanced Chimney Heating Devices on Building Facades - Avlar, Erkan; Korkmaz, Ezgi (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2009)
In Turkey today, with the increase in availability of natural gas, detached heating devices are being preferred over existing heating devices. Due to the lack of chimneys in existing buildings in Turkey or the presence of chimneys that fail to conform to standards, the use of C-type balanced chimney devices has increased. C-type balanced chimney devices take the combustion air directly from the outside by a specific air duct as detached heating equipment, with enclosed combustion chambers and a specific waste gas exhaust duct, and they are ventilated independently of the field of equipment. Because of their essentiality, the use of a chimney is not required in these devices; the waste gas is exhausted through walls, windows, doors, or balconies. The natural gas is a clean fossil fuel that requires no storage in buildings and is easy to use. However, water vapor, carbon dioxide and nitrogen oxides are produced by the combustion of natural gas. It is widely known that high concentrations of these products can have some adverse effects on humans such as dizziness, headaches and nausea. As a result, the waste products could recoil through wall openings on the facade to create unhealthy indoor environments that could be dangerous to human health. Therefore, the importance of standards and regulations about the positional arrangements of the waste gas exhaust ducts of C-type balanced chimney devices on building fagades is increasing. In this research, we analyze the studies of the Institution of Turkish Standards, Chamber of Mechanical Engineers, gas distribution companies, municipalities and authorized firms and compare the criteria to determine the necessary application method. According to our comparison of the references accessed, the criteria are not uniform.
Keywords: C-type balanced chimney devices; natural gas; hermetic systems; Architecture